Investigation on the precursors to and effects of human resource information system use: The case of a developing country - G. M. Azmal Ali Quaosar; Md. Rakibul Hoque; Yukun Bao (Cogent Business & Management, 2018)
There is an inadequate understanding of the successful use and effects of a human resource information system (HRIS) in a developing country context. Given this backdrop, this study aims to explore the precursors to and effects of HRIS use in a developing country. A research model was developed after studying the existing literature, and a questionnaire was developed accordingly to collect data through a purposive sampling method. The research data were obtained from different companies in Dhaka, Bangladesh. The collected data were analyzed using the partial least squares method, a statistical technique based on the structural equation model. The results show that all four hypothesized precursors are significant predictors of the purposes for using an HRIS, and the purposes for using an HRIS are significantly connected to all of the resulting variables except one. The theoretical contribution of this study is that it serves as further evidence for the appropriateness of using Rogers' innovation attributions to gauge different dimensions of the intention to use an HRIS, and Remenyi's and Zuboff's information technology frameworks are used to measure the outcomes of the intention to use an HRIS. The practical contribution of this study is that information technology seems to empower human resources professionals and increase the value of their work. This study adds value to the existing literature on HRISs by focusing on a developing country setting.
Keywords: 650